Measurement of the [lambda]3H lifetime in Au+Au collisions at the BNL relativistic heavy ion collider - Adamczyk, Leszek; Deppner, Ingo Martin; Herrmann, Norbert (Physical review, 2018)
An improved measurement of the 3ΛH lifetime is presented. In this paper, the mesonic decay modes 3ΛH→3He + π− and 3ΛH→d+p+π− are used to reconstruct the 3ΛH from Au+Au collision data collected by the STAR collaboration at Relativistic Heavy Ion Collider (RHIC). A minimum χ2 estimation is used to determine the lifetime of τ=142+24−21(stat.)±29(syst.) ps. This lifetime is about 50% shorter than the lifetime τ=263±2 ps of a free Λ, indicating strong hyperon-nucleon interaction in the hypernucleus system. The branching ratios of the mesonic decay channels are also determined to satisfy B.R.(3He+π−)/(B.R.(3He+π−)+B.R.(d+p+π−))=0.32±0.05(stat.)±0.08(syst.). Our ratio result favors the assignment J(3ΛH)=12 over J(3ΛH)=32. These measurements will help to constrain models of hyperon-baryon interactions.
Im Titel sind "3" und "Lambda" untereinander geschrieben: "3" hochgestellt, "Lambda" tiefgestellt
Im Titel wird Lambda als griechischer Buchstabe dargestellt
Gesehen am 05.07.2019